Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3109/00016341003678443
|View full text |Cite
|
Sign up to set email alerts
|

Frequent inactivation of hSRBC in ovarian cancers by promoter CpG island hypermethylation

Abstract: Our data demonstrate that epigenetic inactivation of hSRBC due to aberrant promoter hypermethylation is a common event and might be implicated in human ovarian tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Several studies have found that down-regulation of SRBC was due to promoter hypermethylation in breast cancer cell lines [Xu et al, 2001;Tong et al, 2010]. We showed here that PTRF, SRBC, and SDPR were down regulated in breast cancer cells.…”
Section: Down-regulation Of Ptrf In Breast Cancer Tissue and Cell Linsupporting
confidence: 63%
“…Several studies have found that down-regulation of SRBC was due to promoter hypermethylation in breast cancer cell lines [Xu et al, 2001;Tong et al, 2010]. We showed here that PTRF, SRBC, and SDPR were down regulated in breast cancer cells.…”
Section: Down-regulation Of Ptrf In Breast Cancer Tissue and Cell Linsupporting
confidence: 63%
“…[136] Cavin3 is frequently inactivated in ovarian cancers. [137] Cavin3 is also down-regulated in breast cancer cell lines and breast tumor tissue. [131] Cavin3 may repress matrix metalloproteinase-9 transcriptional regulation and act as tumor suppressor in controlling the invasive potential of cells.…”
Section: Caveolae New Partners and Cancermentioning
confidence: 99%
“…Silencing of tumor suppressor genes mediated by DNA methylation is a hallmark of human cancer [14]. Lower expression/loss of function due to epigenetic inactivation via aberrant methylation has been reported for RASSF1A [8,15], APC [16], RB1 [11,17], P16 [9] and PRKCDBP [18][19][20], as an important factor for development of various cancers.…”
Section: Introductionmentioning
confidence: 98%